Meningkatkan Kemampuan Pemecahan Matematis Melalui Model Problem Based Learning Dengan Pendekatan Culturally Responsive Teaching Di Kelas Xi-F3 Sman 1 Ingin Jaya - Suryawati Suryawati; Erlina Mariana Erlina Mariana; Desi Yuliana Desi Yuliana; Farach Fazilla Farach Fazilla (Jurnal Pendidikan Nusantara, 2024)
This research was motivated by the low ability to solve mathematical problems in class XI-F3 at SMAN 1 Want Jaya. Therefore, this research was conducted using the Classroom Action Research (PTK) method which consists of two cycles, where each cycle includes planning, implementation, observation and reflection stages. This research aims to improve mathematical problem solving abilities through the application of the Problem Based Learning (PBL) model with a Culturally Responsive Teaching (CRT) approach. Data collection was carried out through tests and documentation, while data analysis used descriptive quantitative techniques. The results of this study showed an increase in classical completeness by 23% between cycle 1 and cycle 2. In cycle 1, classical completeness was recorded at 18 students or 60%, while in cycle 2 it increased to 25 students or 83%. Apart from that, the percentage of problem solving abilities also increased, from 12% in cycle 1 to 82% in cycle 2. Each indicator of the problem solving stage showed positive developments, including: the indicator of understanding the problem increased by 73%, the indicator of planning to solve the problem increased by 79% , the indicator for resolving problems according to plan increased by 70%, and the indicator for checking again increased by 60%.